Beyond the Pixels : Psychographic Profiling of Virtual Influencers’ Followers in Social Media - Thakur, Anand; Singla, Kavita; Singla, Kamini; T., Mohammed Irshad; Kaur, Simran; Kaur, Parwinder (Indian Journal of Marketing, 2025)
Purpose : In the evolving landscape of artificial intelligence (AI), virtual influencer (VI) marketing has surged in popularity on social media platforms. The present study delved into the core determinants influencing social media users’ attitudes toward VIs on Instagram. It categorized the respondents based on their psychographic and demographic attributes. Design/Methodology/Approach : The study employed exploratory factor analysis (EFA) to determine the fundamental dimensions of the influencer’s preferred factors and hierarchical and K-Means cluster analysis to classify 182 followers based on the homogeneity of their attributes. Findings : The EFA findings illuminated four intrinsic dimensions of VIs: (a) attitudinal homophily, (b) aesthetic influence, informativeness, and ad content value, (c) perceived reciprocity, and (d) perceived originality. K-Means clustering classified respondents into two segments: VR enthusiasts and discerning realists. Practical Implications : The study offered useful strategic implications for VI marketing. Marketers refined their criteria for selecting VIs and designed segment-specific marketing campaigns to cater to the distinct preferences of VR enthusiasts and discerning realists. Originality : The originality of this study lies in its comprehensive exploration of the evolving domain of VI marketing within the context of AI advancements.